2020
DOI: 10.1177/1461444820904362
|View full text |Cite
|
Sign up to set email alerts
|

Restricted modes: Social media, content classification and LGBTQ sexual citizenship

Abstract: In the context of recent controversies surrounding the censorship of lesbian, gay, bisexual, transgender and queer online content, specifically on YouTube and Tumblr, we interrogate the relationship between normative understandings of sexual citizenship and the content classification regimes. We argue that these content classification systems and the platforms’ responses to public criticism both operate as norm-producing technologies, in which the complexities of sexuality and desire are obscured in order to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…This policy change made Tumblr's content moderation visible, allowing users to notice and critique its policies, processes, and politics [117]. The ways social media platforms classify content for moderation decisions reinforce norms, obscure complex genders and sexualities, and attempt to construct a "good" LGBTQ+ user by removing adult parts of online presentation [110]. In this way, social media platforms' control of sexual online content limits trans people's online presentation [9].…”
Section: Trans People and Social Media Content Moderationmentioning
confidence: 99%
“…This policy change made Tumblr's content moderation visible, allowing users to notice and critique its policies, processes, and politics [117]. The ways social media platforms classify content for moderation decisions reinforce norms, obscure complex genders and sexualities, and attempt to construct a "good" LGBTQ+ user by removing adult parts of online presentation [110]. In this way, social media platforms' control of sexual online content limits trans people's online presentation [9].…”
Section: Trans People and Social Media Content Moderationmentioning
confidence: 99%
“…In addition, these posts aggregate, bunching together around specific locations, connecting users by cultivating affinities with particular sentiments (particularly mobilising positive experience). Such aggregation also reproduces classifications of 'good' sexual citizens (see also Southerton et al, 2020), through the foregrounding of (hetero)normativities around relationship commitment, and monogamy, for example.…”
Section: Love Notes: Public/private Queer Relationshipsmentioning
confidence: 72%
“…There is a rich recent history of research examining the affective fabrics of digital cultures, including queer engagement with social and other digital media (e.g., Carlson, 2020;Dobson et al, 2018;Haber, 2019;Southerton et al, 2020). Studies have revealed, for example, users' strategic engagement with digital hook-up or dating apps in the pursuit of intimacy, romantic relationships, love and sexual encounters (Albury and Byron, 2016;Møller and Petersen, 2017).…”
Section: Queer Digital Engagement: Technological Affordances Connection and Communitymentioning
confidence: 99%
“…For Participant Sri, the algorithm is only hostile when it threatens her perceptible safety. Without being bothered by YouTube's or Tumblr's censorship of LGBT content and their restricted mode of content classification that governs the norms of what is promoted as acceptable sexual citizenship (Southerton et al, 2021), the curations of Instagram extend her algorithmic imaginary and allow her to safely explore her own limits of LGBT identity. She maintains two Instagram accounts, one of which is private and followed only by close contacts to whom she has disclosed her sexual identity.…”
Section: Findings and Discussionmentioning
confidence: 99%